The Ethics of Protecting Environment Ibn Khaldun Perspective’s: Analysis of Exegesis Maqasidi's QS. al-A'raf Verse 56 - Erika Aulia Fajar Wati; Hakam al-Ma'mun (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2022)
This paper discusses the ethics of protecting the environment according to Ibn Khaldun. Starting from his statement in his magnum opus entitled Muqaddimah, he explained how the orderliness of the universe and everything within is a unified system that is mutually dependent on one another. The order and harmony of the universe are full of endless wisdom and lessons. From this, lessons can be drawn, one of which is that the natural order system reflects the social system prevailing in society. Social systems that rely on each other between individuals will produce a civilized society. So to maintain the order and balance of the environment, the Qur'an through Qs. al-A'raf verse 56 forbids doing damage on earth. Through the maqasidi interpretation approach to the verse, it can be concluded that the main principle of maqasid al-syariah can only be implemented in everyday life if the environment is conducive. Environmental conditions will affect the effectiveness of the application of Islamic law.